(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The poultry industry plays a key role in developing socio-economic and health sectors in Bangladesh. Poultry waste is a potential environmental threat as untreated poultry waste is used in vegetable gardens. The study aimed to investigate the current situation of small-scale poultry farms and their waste management practices in selected areas of Bangladesh and detect Escherichia coli and Salmonella in vegetables from farms using untreated poultry waste as fertilizer. Materials and Methods: A structured questionnaire-based survey was conducted in 86 small scale poultry farms from different upazilas of Mymensingh and Khulna districts. 104 samples, including vegetables, poultry litter, water, and soil, were collected from vegetable gardens, ponds, fields, and wet markets in Mymensingh district to detect microbial contamination. Bacteria were identified based on their growth and colony morphology on selective media and motility tests. The presence of E. coli and Salmonella was confirmed by polymerase chain reaction (PCR) using a commercial PCR kit. Results: The survey revealed that mostly middle-aged males were involved in poultry farming. Most of the farmers had primary education and engaged in farming for about 5 years without training. In the study area, 37% of farmers collected droppings daily in the morning and used them as organic fertilizer. About 58% of farmers did not know the hygienic handlings of droppings and faced health problems. In PCR, either E. coli or Salmonella or both were confirmed in vegetables, litter, soil, and pond water. Conclusion: Appropriate poultry waste management practices can reduce the possible contamination of microbial agents in the human food chain. J. Adv. Vet. Anim. Res., 10(1): 72–79, March 2023 http://doi.org/10.5455/javar.2023.j654